The Influence Of TGT And NHT Cooperative Learning On Improving Science Learning Outcomes Of Elementary Students - Ita Nurtianingsih; Otib Satibi Hidayat; Dodi Sukmayadi (Universitas PGRI Adi Buana Surabaya, 2023)
This study aims to obtain data on the effect of the TGT (Teams-Games Tournament) and NHT (Numbered Head Together) cooperative learning models on improving science learning outcomes for fifth grade students. This research was conducted on students who were registered as students in the 2022/2023 Academic Year. This research was conducted from October to December 2022. The research method used in this study is a quantitative method with a (t-test). The total population 396 and sample of 58 students obtained randomly. The instrument used is a multiple choice test with answer choices a, b, c, and d. Based on the results of the hypothesis testing of the experimental 1 group and the experimental 2 group, tcount = 3.749 was obtained, then table was obtained with a result = 1.997. Thus it can be stated that there is a positive influence between the variables of cooperative learning type TGT (Teams-Games Tournament) and NHT (Numbered Head Together) learning models and the variables of science learning outcomes. Thus the conclusion of this study is that there is an influence of the TGT (Teams-Games Tournament) and NHT (Numbered Head Together) type group learning models on the learning outcomes of class V students in Gugus III MuaraGembong Bekasi District.